Genetic and healthy lifestyle factors in relation to the incidence and prognosis of severe liver disease in the Chinese population - Pang, Yuanjie; Lv, Jun; Kartsonaki, Christiana; Yu, Canqing; Guo, Yu; Chen, Yiping; Yang, Ling; Millwood, Iona Y.; Walters, Robin G.; Lv, Silu; Burgess, Sushila; Sansome, Sam; et al. (Chinese medical journal, 2023)
Severe liver disease (SLD), including cirrhosis and liver cancer, constitutes a major disease burden in China. We aimed to examine the association of genetic and healthy lifestyle factors with the incidence and prognosis of SLD. The study population included 504,009 participants from the prospective China Kadoorie Biobank aged 30-79 years. The individuals were from 10 diverse areas in China without a history of cancer or liver disease at baseline. Cox regression was used to estimate adjusted hazard ratios (HRs) for incident SLD and death after SLD diagnosis associated with healthy lifestyle factors (smoking, alcohol, physical activity, and central adiposity). Additionally, the contribution of genetic risk for hepatitis B virus (HBV, assessed by genetic variants in major histocompatibility complex, class II, DP/DQ [ HLA - DP / DQ ] genes) was also estimated. Compared with those with 0-1 healthy lifestyle factor, participants with 2, 3, and 4 factors had 12% (HR 0.88 [95% confidence interval [CI] 0.85, 0.92]), 26% (HR 0.74 [95%CI: 0.69, 0.79]), and 44% (HR 0.56 [95%CI: 0.48, 0.65]) lower risks of SLD, respectively. Inverse associations were observed among participants with both low and high genetic risks (HR per 1-point increase 0.83 [95%CI: 0.74, 0.94] and 0.91 [95%CI: 0.82, 1.02], respectively; Pinteraction = 0.51), although with a non-significant trend among those with a high genetic risk. Inverse associations were also observed between healthy lifestyle factors and liver biomarkers regardless of the genetic risk. Despite the limited power, healthy lifestyle factors were associated with a lower risk of death after incident SLD among participants with a low genetic risk (HR 0.59 [95%CI: 0.37, 0.96]). Lifestyle modification may be beneficial in terms of lowering the risk of SLD regardless of the genetic risk. Moreover, it is also important for improving the prognosis of SLD in individuals with a low genetic risk. Future studies are warranted to examine the impact of healthy lifestyles on SLD prognosis, particularly among individuals with a high genetic risk.